Divine retribution: A defence - Crisp, Oliver (Sophia, 2003)
The concept of divine justice has been the subject of considerable scrutiny in recent philosophical theology, as it bears upon the notion of punishment with respect to the doctrine of eternal damnation. In this essay, I set out a version of the traditional retributive view of divine punishment and defend it against one of the most important and influential contemporary detractors from this position, Thomas Talbott. I will show that, contrary to Talbott’s argument, punishment may satisfy divine justice, and that perfect justice is commensurate with retribution, rather than, as he suggests, reconciliation and restoration.